Eschatological doctrines in the writings of John and Charles Wesley - Downes, J. Cyril (The University of Edinburgh, 1960)
Chapter One. • • Introduction: Strangers and Pilgrims. 1. • PART ONE. PRESENT SALVATION. • • • Introduction: Realized Eschatology. 14. • Chapter Two. Justification and Regeneration. 19. • • Chapter Three. Sanctlfication. 42. • • Chapter Four. Holy Communion. 71. • • PART TWO. FINAL SALVATION. • • • Chapter Five. Death and Resurrection. 87. • • - The Resurrection of the Body. 114. • Chapter Six. The Coming of Christ in Judgment. 124. • • - The Final Coming of Chrisi. 124. - The Judgment. 136. Chapter Seven. The End of the World. 356. • • - The Millennium. 162. • - The Restoration of All Things. 169. • - The Final Victory. 174. • Chapter Eight. Hell. 180. • • - Satan and his Evil Angels. 205. • Chapter Nine. Heaven. 216. • • - The Communion of Saints. 234. • - Good Angels. 240. • - Eternity. 245. • Chapter Ten. Conclusion. 248. • • - The Place of the Eschatological Doctrines in Wesley's Theology. 248. • - Wesley and Modern Theology. 253. • Appendix - Wesley's View of the Scriptures, 261.. •. • Bibliography. 269.